2020
DOI: 10.1038/s41467-020-16818-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid glacier retreat and downwasting throughout the European Alps in the early 21st century

Abstract: Mountain glaciers are known to be strongly affected by global climate change. Here we compute temporally consistent changes in glacier area, surface elevation and ice mass over the entire European Alps between 2000 and 2014. We apply remote sensing techniques on an extensive database of optical and radar imagery covering 93% of the total Alpine glacier volume. Our results reveal rapid glacier retreat across the Alps (−39 km² a −1) with regionally variable ice thickness changes (−0.5 to −0.9 m a −1). The strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(106 citation statements)
references
References 52 publications
7
99
0
Order By: Relevance
“…Here the ablation is likely enhanced because of the reflection of radiation (Hock, 2005). Since 2011 onwards, we observed that concave shapes have become more pronounced, ice velocities decreased generally, and the glacier surface downwasted as observed at other glaciers (Ragettli et al, 2016;Sommer et al 2020). The decreased ice velocities are likely a consequence of the downwasting.…”
Section: Annual Glacier-wide Mass Balances Ela and Aarsupporting
confidence: 61%
“…Here the ablation is likely enhanced because of the reflection of radiation (Hock, 2005). Since 2011 onwards, we observed that concave shapes have become more pronounced, ice velocities decreased generally, and the glacier surface downwasted as observed at other glaciers (Ragettli et al, 2016;Sommer et al 2020). The decreased ice velocities are likely a consequence of the downwasting.…”
Section: Annual Glacier-wide Mass Balances Ela and Aarsupporting
confidence: 61%
“…However, exercising in natural environments is not only affected by urbanization but also by climate change. Alpine environments are especially prone to climate change vulnerability (7), where glacier retreat, less snowfall at lower altitudes and massive changes in the snow line were reported (8,9). Large decreases of amount and duration of snow will be seen below 1,500-2,000 m altitude and snow amount will also decline at altitudes of 2,000 m above sea level within the next decades (8).…”
Section: Introductionmentioning
confidence: 99%
“…Large decreases of amount and duration of snow will be seen below 1,500-2,000 m altitude and snow amount will also decline at altitudes of 2,000 m above sea level within the next decades (8). This impact is accompanied with various severe consequences for people, such as water resource management, risk assessments, economic changes or tourism (9,10). Based on economic cost models, climate change will affect the ski industry and skiing tourism negatively within the 21st century (11).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of climate change are widespread and clearly visible in the Alps (Rogora et al, 2018) but particularly evident in the dwindling glacier resources (Sommer et al, 2020;Zekollari et al, 2019). Over the past 100 years, the temperature in the Alps has increased almost twice as fast compared to the global average, resulting in nearly 2 °C higher mean air temperatures (Auer et al, 2007;Marty and Meister, 2012).…”
Section: Introductionmentioning
confidence: 99%